Liquid biopsy in the clinical management of bladder cancer: current status and future developments. (1st February 2020) - Kouba, Erik; Lopez-Beltran, Antonio; Montironi, Rodolfo; Massari, Francesco; Huang, Kun; Santoni, Matteo; Chovanec, Michal; Cheng, Michael; Scarpelli, Marina; Zhang, Jie; Cimadamore, Alessia; Cheng, Liang
ABSTRACT: Introduction : The use of liquid biopsy on the blood from solid malignancies provides a convenient way of detecting actionable mutations, monitoring treatment response, detecting early recurrence and prognosticating outcomes. The aim of this review is to discuss the current status and future direction of serum biomarkers in the clinical management of urinary bladder cancer. Areas covered : This review provides an overview of blood liquid biopsy and bladder cancer using methods of circulating tumors cells, circulating RNA, serum metabolites and cell-free DNA. Recent clinical studies and advances in methodology are emphasized. We performed a literature search using PMC/PubMed with keywords including 'liquid biopsy', 'circulating tumor DNA', 'cell-free DNA', 'biomarkers', 'bladder cancer' 'precision medicine'. Additional articles were obtained from the cited references of key articles. An emphasis was placed on recent studies published since 2018. Expert opinion : Liquid biopsies represent a potential biomarker using cell-free DNA, metabolomic profiles of altered cellular metabolism, circulating cancer cells and RNA. Despite displaying tremendous clinical promise, the current status of the blood liquid biopsies has not reached fruition. However, future investigations should lead the evolution of liquid biomarker into clinical utility for the management of bladder cancer.